Minute virus of mice transcriptional activator protein NS1 binds directly to the transactivation region of the viral P38 promoter in a strictly ATP-dependent manner. - Christensen, J (1995)
The NS1 polypeptide of minute virus of mice (MVM) is a potent transcriptional activator of the MVM P38 promoter. The minimum region of this promoter required for transactivation has been identified and termed the transactivation region (tar). However, the function of tar and the biochemical steps involved in NS1-mediated transactivation are not well understood. Here we provide evidence that NS1 binds directly and specifically to tar in a strictly ATP-dependent manner. A DNA fragment containing tar was specifically coimmunoprecipitated with purified baculovirus-expressed MVM NS1, using antibodies directed against NS1 amino- or carboxy-terminal peptides. Using this immunoprecipitation assay, we found that the NS1-tar interaction was enhanced approximately 10-fold by ATP, but subsequent incubation at elevated temperatures in the presence, but not the absence, of MgCl2 caused rapid loss of tar binding. This finding suggests that the tar-NS1 complex has a short half-life under assay conditions which favor ATP hydrolysis. Specific binding was efficiently inhibited by self-ligated oligonucleotides containing the core DNA sequence (ACCA)3, but the same nonligated 20- and 21-mer oligonucleotides were unable to compete effectively, indicating that NS1 only binds to its cognate site when this site is presented on DNA fragments of sufficient size. DNase I footprinting experiments performed in the presence of gamma S-ATP revealed that NS1 protects a 43-bp sequence extending asymmetrically from the (ACCA)2 sequence toward the TATA box of the promoter. NS1 footprints obtained at other sites in the MVM genome were similarly large and asymmetric, all extending approximately 31 bp 5' from the core (ACCA)2-3 sequence. Surprisingly, no footprints were obtained in the absence of gamma S-ATP even under low-stringency binding conditions. However, ATP could be omitted from the reactions if NS1 was first incubated with antibodies directed against its 16-amino-acid carboxy-terminal peptide. Since these antibodies probably create intermolecular cross-links, this finding suggests that NS1 may only bind its cognate site efficiently, or perhaps at all, if the transactivator is first induced to form oligomers. From these data, we hypothesize that ATP binding may also induce NS1 to oligomerize and that such assembly is required before the protein can bind effectively to the tar sequence. The functional implications of the NS1-tar interaction will be discussed.